2014
DOI: 10.17795/whb-23651
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Sleep and Its Related Factors in Postmenopausal Women in West Tehran

Abstract: Background: Sleep disturbance is common in menopausal women. Objectives: This study aimed to measure the rate of self-reported sleep disturbance and to identify its associated factors in 50-60 year-old women. Patients and Methods:This cross-sectional study included 700 healthy volunteer women aged 50 to 60 years, who were in postmenopausal period for at least 1 year. The participants were interviewed after obtaining informed consents. The study questionnaire covered two main aspects of personal characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…This finding is consistent with the previous research into the brain area, indicating that sleep disorders are more common in menopausal women [11,23], while in line with the study by Golyan Tehrani, which showed the prevalence of insomnia to be high in menopausal women [24].…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This finding is consistent with the previous research into the brain area, indicating that sleep disorders are more common in menopausal women [11,23], while in line with the study by Golyan Tehrani, which showed the prevalence of insomnia to be high in menopausal women [24].…”
Section: Resultssupporting
confidence: 93%
“…Considering that adequate sleep is essential to physical and mental health and menopausal women may experience sleep disorders, attention should be paid to their lifestyle and educational interventions to improve the possible sleep problems. According to the findings of Taavoni et al (2014) 70% of menopausal women have sleep disorders [11], while Sussman et al (2015) have reported that 17% of menopausal women have insomnia [12]. Furthermore, the results obtained by Nisar and Sohoo have indicated that 85.3% of premenopausal women and 79.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…They also noted that menopause has a significant role in altering sleep structure among female elderly people so much so that after menopause, women suffer from different sleep problems such as long sleep latency, frequent nighttime awakenings, and shorter sleep (26). Taavoni et al also reported that 70% of healthy menopausal women in Tehran, Iran, suffered from sleep disorders (27). Similarly, Kravitz et al showed that sleep disorders become more common during menopause transition so much so that 38% of menopausal women suffer from these disorders (28).…”
Section: Discussionmentioning
confidence: 97%